KUALITAS INDUK UDANG WINDU (Penaeus monodon) DI PERAIRAN PANTAI PANGANDARAN, SELATAN JAWA BARAT - Sachoemar, Suhendar I; aliah, ratu siti (Jurnal Sains dan Teknologi Indonesia, 2010)
An evaluation of the quality of the Black Tiger Broodstock Shrimp (Penaeus monodon) in the southern coastal area of Pangandaran, West Java was conducted during period of Juny-October 2005. The evaluation was focused on the waterquality identification and the quality of the broodstock collected from the farmer sorround the Pangandaran Area. The result of the evaluation showed that the water quality of the coastal area of Pangandaran was good compare to the northern coastal area of West Java in which the organic and inorganic pollutantwas . This situation was affected on the quality of the broodstock. The identification result on the quality of broodstock using polymerase chain reaction (PCR) method shows that the broodstock shrimp of the Black Tiger Shrimp(Penaeus monodon) in the coastal area of Pangandaran is free from the White Spot Syndrome Virus (WSSV) and Infectious Hypodermal and Hematopoietic Necrosis Virus (IHHNV). From 99 broodstock identified, only 4 indicated by very light contaminated WSSV and 2 by IHHNV. This condition shows that in general the quality of the broodstock shrimp of the Black Tiger Shrimp (Penaeus monodon) in the coastal area of Pangandaran was excellent and these sources are potentialto be applied as broodstock sources for developing the Black Tiger Shrimp (Penaeus monodon) culture in the national level.